To rewrite \(\log_7(a^4 b^{14})\) using the Quotient Rule of Logarithms, we'll apply the properties of logarithms.
Firstly, we use the product rule: \[ \log_b(mn) = \log_b(m) + \log_b(n) \] So, we can split \(\log_7(a^4 b^{14})\) as follows: \[ \log_7(a^4 b^{14}) = \log_7(a^4) + \log_7(b^{14}) \]
Next, we apply the power rule of logarithms: \[ \log_b(m^k) = k \log_b(m) \] This means we can rewrite \(\log_7(a^4)\) and \(\log_7(b^{14})\): \[ \log_7(a^4) = 4 \log_7(a) \] \[ \log_7(b^{14}) = 14 \log_7(b) \]
Putting it all together, we have: \[ \log_7(a^4 b^{14}) = 4 \log_7(a) + 14 \log_7(b) \]
Thus, the correct response is: 4log7a + 14log7b.